Recent Estimates of Exchange Rate Pass-Through to Import Prices in the Euro Area - Nidhaleddine Ben Cheikh; Christophe Rault (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper provides an update on the exchange rate pass-through (ERPT) estimates for 12 euro area (EA) countries. First, based on quarterly data over the 1990-2012 period, our study does not find a significant heterogeneity in the degree of pass-through across the monetary union members, in contrast to previous empirical studies. As we use a longer time span for the post-EA era than existing studies, this is not surprising, since the process of monetary union has entailed some convergence towards more stable macroeconomic conditions across EA member states. Second, when assessing the stability of pass-through elasticities, we find very weak evidence of a decline around the inception of the euro in 1999. However, our results reveal that a downtrend in ERPT estimates became apparent starting from the beginning of the 1990s. This observed decline was synchronous to the shift towards reduced inflation regimes in our sample of countries. Finally, we notice that the distinction between “peripheral” and “core” EA economies in terms of pass-through has significantly decreased over the last two decades.
Keywords: E31; F31; F40; 330; exchange rate pass-through; import prices; Euro area